Analisis Beban Pajak Paska Kenaikan PPN 12% pada Sektor Perdagangan (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2026)
This study aims to explain the context of the Value Added Tax (VAT) increase policy and its relevance to the trade sector, while also presenting a framework for analyzing the tax burden. The data sources used consist of publications from the last four years, namely from 2021 to 2024. The observed phenomena are then analyzed using various secondary data obtained from scientific journals, official government reports, and other reliable sources relevant to the research topic, in order to provide a comprehensive overview. The conclusions are drawn based on empirical facts, the impacts of the tax increase, and the government’s mitigation efforts to ensure taxpayer compliance. The increase in the VAT rate represents an important step in fiscal reform aimed at increasing state revenue and reducing the budget deficit. This policy has significant potential to support the growth of the national budget, particularly in financing priority sectors such as infrastructure, education, and healthcare. However, the VAT increase may also affect consumers’ purchasing power and trade activities, thus requiring appropriate supporting policies to minimize negative impacts. Therefore, it is expected that this policy will contribute to sustainable economic stability and promote long-term national economic growth.